CHEMICAL COMPOSITION AND IRRIGATIVE CHARACTERISTIC OF THE BABOLROUD RIVER WATER (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Hydrochemical composition and irrigative quality of the river Babolroud were studied. It was revealed that technogenic factor does not evidently affect the chemical composition of the river Babolroud, as the chemistry of the river’s water fits to the water quality formed under the impact of natural factors. According to the composition of the main ions, the value of the total mineralization, water pH, irrigation coefficient and ions correlation, the water of the Babolroud river has a good irrigation quality.
Keywords: irrigative quality of the river Babolroud; irrigation coefficient; ions correlation